Calculation of the resistance force of tree crown with regard to its fractal structure - Rebko Дмитрий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
Model is considered as the crown of the tree fractal object. Problem airflow through the crown of the tree is solved on the basis of probabilistic concepts, just as it is done in the analysis of particle scattering and absorption of radiation. A special case when the shape of the tree crown - a triaxial ellipsoid. The dependence of the drag force of the air velocity through the crown.